Ultra fine pitch Cu wire bonding on C45 ultra low k wafer technology - Leng E.P.; Siong C.T.; Seong L.B.; Leong P.; Gunasekaran; Song J.; Mock K.S.; Siew C.W.; Sivakumar; Kid W.B.; Weily C. (2023)
As gold price continues to move in an overall rising trend, conversion to Cu wire has been given great focus as the main effort for cost reduction. Cu is a good alternative due to 26% lower electrical resistivity than Au, hence much higher electrical conductivity. However, Cu free-air-ball and bonded ball hardness are 34% and 60% higher than that of Au, hence increases the stress on bond pad and chip. Although Cu wire price is generally only 5 to 10% of Au wire cost depending on wire diameter, but bonding with a much harder material like Cu requires great characterization effort due to the a much higher level of unknowns and complexities, especially when dealing with ultra fine pitch and ultra low k wafer technology. This study is aimed to share the success story of Cu wire bond process characterization for C45 ultra low k wafer technology with bond-over-active bond pads, on a thermally enhanced BGA package with 31x31mm large body size. With Al bond pad thickness at 2.1um, the combination in this study represents the highest difficulty level in Cu wire bonding due to potentially high pad damage and Al splash, and possibly higher bond failure due to BGA substrate outgasing. Along with the challenging wafer technology comes the small bond pad opening at 40um. In view of such small bond pad opening, and a typically higher Al splash with Cu wire, hence the maximum ball size was targeted at 30um. Wire diameter was fixed at 18um to ensure good wire-to-bonded ball ratio, as well as to allow a good capillary design. The latest generation wire bonder was used to ensure the best bond placement accuracy at +/- 2um, as well as to minimize bond pad damage through higher bond force resolution. The characterization process started with selection of capillary, followed by selection of Cu wire, both with certain level of bonding parameters optimization. For capillary selection, the best 3 capillaries with high success rate in the semiconductor industry for Cu wire bonding were selected. Each of the capillary had different features as a technology edge from the different suppliers. The key responses were 2nd bond peel strength and 1st bond Al remnant. Out of the 3 capillaries, the best was selected based on highest 2nd bond peel and Al remnant through a thorough DOE process. During this stage, it was also found that Cu Kit with an extended coverage at bonding zone was an important factor to prevent FAB oxidation during bonding, hence helped to reduce Al splash. Upon completion of capillary selection, the characterization work continued with wire selection. 3 wire types were studied, i.e. 2 4N Cu wire from different supplier, and 1 Pd coated 4N Cu wire. Pd coated wire was selected as one of the candidate to prevent oxidation on Cu wire surface, hence allowing a better 2nd bond peel strength. The key responses were bond pad peeling and lifted bond after thermal aging at 175 deg C for 168hrs. However, this study showed that Pd coated wire had much higher bond pad damage due to harder free-air-ball hardness even after parameters DOE. Out of the 2 4N Cu wire, 1 emerged to be more superior with zero bond pad peeling and lifted ball failure after the said thermal aging test. As part of the wire selection process, manufacturing robustness was also tested with a bigger sample size build which includes wire bond process UPH, MTBA & yield. After an overall study, it was found that 1 of the 2 4N Cu wire performed better and hence was selected to proceed with qualification. In summary, the most challenging ultra fine pitch Cu wire bonding process on C45 ultra low k wafer technology in BGA can be made possible through a detailed process characterization and careful consideration of manufacturing performance. 2010 IEEE.